The Implementation of Interactive Learning Media Utilizing Quizizz at SMAN 2 Rambah - Yunita, Nova; Amelia Chandra, Detri (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
The aim of this research is to find out how effective the use of Quizizz-based interactive learning media is by class XI Science students at SMAN 2 Rambah in the Informatics subject with computer network material. A quantitative method was used, with a questionnaire created by the school's Guidance and Counseling (BK) teacher to measure the level of student boredom before and after Quizizz. A Likert scale was used for data collection. Descriptive analysis, normality test, homogeneity of variance test, and difference test (paired sample t-test) were used to analyze the data obtained. All these techniques are used with the help of the SPSS program. The results show that Quizizz increases student participation in learning and significantly reduces student boredom. Before Quizizz was used, the average burnout score was 41.96. However, after use, this score dropped to 19.79. It was shown by the difference test that this difference was significant (p < 0.05). With this reduction in boredom levels, it is clear that Quizizz not only makes learning more interesting, but also makes learning fun and competitive. However, obstacles such as teachers' limited digital skills and difficulties in obtaining technology in remote areas still need to be overcome. According to this research, Quizizz can be a great interactive learning tool that gets students more engaged in learning, especially in high school.